Pelatihan Pengelolaan Keuangan Berbasis Budaya Lokal Pada UMKM Annisa Jepara Furniture - Darmawati; Indrijawati, Aini; Sundari; Kusumawati, Andi; Juanda, Juanda (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2024)
Community service UMKM Annisa Jepara Furniture can maximize entrepreneur income with proper financial management. The purpose of this Community service is to make a solid partner in financial management; record transactions and preparation of financial reports; and calculate the cost of production. The methods used in implementing Community service are lectures, discussions, workshops, and tutorials in preparing financial reports. This activity was carried out in three stages, namely: observation, implementation, and evaluation. The results achieved were the participants were skilled in financial management; recording of transactions and preparation of financial reports; and making the calculation of the cost of production of furniture. Outputs are publications in online media Barru Pos and YouTube videos.